Impact of Escherichia coli K12 and O18:K1 on human platelets: Differential effects on platelet activation, RNAs and proteins. Issue 1 (December 2018) - Fejes, A.; Best, M.; van der Heijden, W.; Vancura, A.; Verschueren, H.; de Mast, Q.; Wurdinger, T.; Mannhalter, C.
Abstract Blood platelets can interact with bacteria, possibly leading to platelet activation, cytokine and microparticle release and immune signalling. Besides, bacteria can also affect the platelet RNA content. We investigated the impact of non-pathogenic K12 and pathogenic O18:K1Escherichia (E.) coli strains on platelet activation, RNA expression patterns, and selected proteins. Depending on bacteria concentration, contact of platelets withE. coli K12 lead to an increase of P-selectin (24–51.3%), CD63 (15.9–24.3%), PAC-1 (3.8–14.9%) and bound fibrinogen (22.4–39%) on the surface.E. coli O18:K1 did not affect these markers. Sequencing analysis of total RNA showed thatE. coli K12 caused a significant concentration change of 103 spliced mRNAs, of which 74 decreased. For the RNAs ofHMBS (logFC = +5.73), ATP2C1 (logFC = −3.13) andLRCH4 (logFC = −4.07) changes were detectable by thromboSeq and Tuxedo pipelines. By Western blot we observed the conversion of HMBS protein from a 47 kDA to 40 kDa product byE. coli K12, O18:K1 and by purified lipopolysaccharide. While ATP2C1 protein was released from platelets, E. coli either reduced the secretion or broke down the released protein making it undetectable by antibodies. Our results demonstrate that differentE. coli strains influence activation, RNA and protein levels differently which may affect platelet-bacteria crosstalk.